PERLINDUNGAN HUKUM BAGI PENGGUNA TRANSPORTASI ONLINE ATAS TINDAKAN PEMOTONGAN SALDO SEPIHAK TERHADAP PEMBATALAN PESANAN DITINJAU DARI UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Marchelina Theresia; ve Wheni Setijawati Soemarwi (Fakultas Hukum Universitas Tarumanagara, 2021)
Technological developments have had a great impact on the transportation sector, which can be seen in the provision of online transportation services. With the many conveniences provided for consumers who use online transportation, it is undeniable that the use of these services can cause a loss for consumers. Where there is a case of cutting balances for unilaterally canceling orders by online transportation service providers which makes consumers experience a loss. In this case the consumer feels aggrieved and demands compensation, but the online transportation party does not provide compensation as it should. This makes the online transportation party violate the regulations that have been regulated in Law Number 8 of 1999 concerning Consumer Protection. The purpose of this research is to find out how the legal protection for online transportation users is for the act of unilaterally cutting balances against order cancellations in terms of Law Number 8 of 1999 concerning Consumer Protection. This research uses normative legal research, with a legal approach. The results of this study indicate that online transportation service providers must provide compensation to consumers as a form of legal protection for unilateral cutting of balances against order cancellation